Pendidikan Agama Kristen dan Identitas Generasi Z: Studi tentang Pengaruh Budaya Populer terhadap Pemahaman Nilai-nilai Kristiani - Barbara Green Winslet Bessie; Neti Saekoko; Andrian Wira Syahputra (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study explores how popular culture influences Generation Z's understanding of Christian values, a generation raised in the digital age with unlimited information access. Generation Z possesses unique traits, including strong technological skills, multitasking abilities, and quick reactions to social issues. However, they also tend to be individualistic, less independent, and have limited social skills. Popular culture, heavily influenced by mass media and digital trends, significantly shapes the identity and values of Generation Z. This culture often promotes individualism, materialism, and hedonism, which conflict with Christian values like love, humility, and service. Consequently, Generation Z may struggle to understand and apply Christian values in their lives. The study employs a literature review method to gather information from various sources regarding the impact of popular culture on Generation Z's grasp of Christian values. Findings suggest that popular culture can obscure their understanding of these values, leading them to prefer spectacular and emotional spiritual experiences over a deeper understanding of doctrine. Therefore, Christian Religious Education (PAK) plays a crucial role in assisting Generation Z in comprehending and embodying Christian values. PAK must adopt relevant and engaging strategies, utilizing digital media and interactive learning methods. Additionally, it should foster critical thinking skills, enabling Generation Z to differentiate between Christian values and those that conflict with them.